A robust PN code tracking algorithm for frequency selective Rayleigh-fading channels. - El-Tarhuni, M. (IEEE Transactions on wireless communications)
In this letter, we propose a new tracking scheme that is robust against multipath fading for pseudonoise (PN) code tracking in direct-sequence-spread spectrum systems. The proposed scheme employs an adaptive filter whose taps are adapted using a block least-mean square algorithm and it results in minimizing the effect of multipath interference on the tracking performance. We show that the mean-squared tracking error performance of the proposed scheme is not affected by the presence of closely spaced paths (e.g., one to three chips), unlike that of conventional delay locked loops. We also show that the tap-weight distribution of the filter provides accurate estimates of the multipath delays. For example, at Eb/N0=5 dB, 98% of the time the path estimates lie within one sample (1/5 of a chip) from the actual delays. Furthermore, simulation results suggest that multipath delays over a wide range of terminal speeds can be tracked successfully. The proposed scheme is well suited for wideband code-division multiple-access systems where a large number of closely-spaced multipath components need to be tracked and used in RAKE combining.